Subsidies for renewable energies in the presence of learning effects and market power - Johanna Reichenbach; Till Requate (Kiel Institute for the World Economy (IfW), 2011)
We study the impact of learning by doing, learning spill-overs, and imperfect competition in a model with two types of electricity producers, an oligopolistic sector of polluting fossil-fuel utilities and a competitive fringe of non-polluting generators of electricity from renewable energy sources (RES-E). Furthermore we consider an upstream industry of RES-E equipment producers engaged in learning by doing. We show that a first-best policy requires two instruments, a tax in the fossil-fuel sector and an output subsidy for RES-E equipment producers. We then study second-best-optimal feed-in tariffs that are paid to the generators of RES-E. By means of simulations we calculate the welfare loss of a second-best-optimal feed-in-tariff policy and analyze how market structure impacts on second-best-optimal feed-in tariffs.
Keywords: Q42; L13; O38; 330; Feed-in tariffs; environmental subsidies; learning by doing; spill-overs; market structure; Förderung regenerativer Energien; Stromtarif; Administrierter Preis; Second Best; Ökosteuer; Steuerwirkung; Energietechnik; Regenerative Energie; Lernprozess; Marktstruktur; Theorie